2015
DOI: 10.1121/1.4906259
|View full text |Cite
|
Sign up to set email alerts
|

Duration of voicing and silence periods of continuous speech in different acoustic environments

Abstract: This work deals with the duration of voicing and silence periods of continuous speech in rooms with very different reverberation times (RTs). Measurements were conducted using the Ambulatory Phonation Monitoring (APM) 3200 (Kaypentax, Montvale, NJ) and Voice-Care devices (developed at the Politecnico di Torino, Italy), both of which have a contact microphone placed on the base of the neck to detect skin vibrations during phonation. Six university professors and 22 university students made short laboratory mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…A similar trend was found by Astolfi et al 2 , although in the present study higher D t_p values were observed. In this study, the speech material was a read text, while Astolfi et al 2 used free speech. This difference in the speech material may have caused the differences in the range of D t_p values.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…A similar trend was found by Astolfi et al 2 , although in the present study higher D t_p values were observed. In this study, the speech material was a read text, while Astolfi et al 2 used free speech. This difference in the speech material may have caused the differences in the range of D t_p values.…”
Section: Discussionsupporting
confidence: 93%
“…This vocal output is affected by various factors such as the type of environment 12 and interlocutor. 3 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, researchers are often interested in speech modifications due to different room acoustics or noise conditions (Astolfi et al, 2015), where speech level difference is mainly investigated.…”
Section: Introductionmentioning
confidence: 99%
“…For example, people tend to increase their voice level in noisy conditions, and this effect is well-known as the Lombard reflex. 13 In general, high noise levels and very long or very short reverberation times may bring to negative effects on the teachers' vocal load demand [14][15][16] and on the academic attainment of pupils. 17 Bottalico and Astolfi 18 used an APM 3200 to collect voice monitorings of 40 teachers from two primary schools that had different acoustic conditions.…”
Section: Introductionmentioning
confidence: 99%